Design and Construction of Traditional Tribal Musical Instruments in Sumbawa With Augmented Reality Technology Android-Based - Ismiyarti, Wilia; Irawati, Irawati; Ismail, Ismail (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Areas of various tribes have distinctive characteristics, such as those of the Sumbawa tribe. Dance arts and traditional tools are elements of the Sumbawa tribal culture. Apart from dance and traditional instruments, the Sumbawa tribe has unique arts, which we generally know as fairy tales (Sakeco), accompanied by the conventional Rebana musical instrument. The culture of the Sumbawa tribe is preserved by building an art studio as a place for its preservation. Sumbawa Regency, especially in Alas District, has a studio called Kemban Alas Art Studio. We can see cultural preservation using modern technology through social media, such as Facebook, Instagram, and TikTok. However, there is still very little preservation through social media regarding Sumbawa culture, such as the content in the press itself due to the influence of new cultures, which has caused the culture of various tribes, especially the Sumbawa tribe, to be little known by most people. The method used in this research is developing the Waterfall model of LifeL Cycle (SDLC) Software and qualitative data collection. This research aims to build an Android-based Augmented Reality application at the Kemban Alas Art Studio and assist the Art Studio in educating Sumbawa tribal culture using the Augmented Reality application. The result of this research is that researchers have completed the design and development of an application that uses Android-based Aulgmelnteld Reality technology as a medium for introducing the traditional music tool Sulkul Sulmbawa.